2023
DOI: 10.3390/polym15030535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 Nanoparticles and Extrusion Process on the Physicochemical Properties of Biodegradable and Active Cassava Starch Nanocomposites

Abstract: Biodegradable polymers have been strongly recognized as an alternative to replace traditional petrochemical plastics, which have become a global problem due to their long persistence in the environment. In this work, the effect of the addition of titanium dioxide nanoparticles (TiO2NP) on the morphology, physicochemical properties and biodegradation under industrial composting conditions of cassava starch-based nanocomposites obtained by extrusion at different screw speeds (80 and 120 rpm) were investigated. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…These results are outstanding compared to the literature, where most research obtains lower ε b values with the incorporation of nanoparticles, attributing this behavior to the early fissure due to the NP agglomerates. [ 31,60,61 ] The great synergistic effect of the layers was observed in the bilayer material that presented the highest values of ε b and tensile toughness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are outstanding compared to the literature, where most research obtains lower ε b values with the incorporation of nanoparticles, attributing this behavior to the early fissure due to the NP agglomerates. [ 31,60,61 ] The great synergistic effect of the layers was observed in the bilayer material that presented the highest values of ε b and tensile toughness.…”
Section: Resultsmentioning
confidence: 99%
“…This concentration is also recognized as safe (GRAS) by FAO and the World Health Organization. [29][30][31] To the best of our knowledge, the effect of using two layers based on starch films with different types of functionalities that may confer activity and better physicochemical properties on a bilayer material has not been studied. Hernández-García et al (2022) investigated a biodegradable bilayer film from a starch layer with polyphenols-gellan gum and a polyesters blend layer with commercial ferulic acid, p-coumaric, or protocatechuic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior has been observed in starch nanocomposites with 1 wt.% of TiO 2 NP by Iacovone et al (2022) but it is not very common in the literature. [71][72][73] The authors suggested that this fact could be related to the effect of hydrolytic degradation, since the nanoparticles may accelerate some hydrolytic reactions. Water and microorganisms could damage the interface between the starch matrix and nanoparticles, increasing the possibility of hydrolysis.…”
Section: Biodegradationmentioning
confidence: 99%
“…The antimicrobial activities of the films showed that there were inhibitory zones around the circular film disk, which can be attributed to the addition of TiO 2 nanoparticles. Iacovone et al 32 studied the effect of adding titanium dioxide nanoparticles (TiO2) on morphology, physicochemical properties, and biodegradation under industrial composting in cassava starch-based films obtained by extrusion at different screw speeds (80 and 120 r/min). The films produced at 120 r/min showed fully processed starch and homogeneously distributed nanoparticles, leading to greater flexibility than those obtained at 80 r/min.…”
Section: Introductionmentioning
confidence: 99%